Research on primary frequency regulation strategies for ancillary wind power inertia based on the rotor kinetic energy - Sun, Li; Yang, Peihong; Jiang, Hui; Xu, Yanfang; Kang, Lan; Lu, Xiuyan (Frontiers in Energy Research, 2023)
The additional frequency control of wind turbine is an effective method to solve the problem of low inertia in power system with high proportion of new energy. The primary frequency regulation of wind power inertia auxiliary system based on rotor kinetic energy can not only make the wind turbine run at the maximum power point, but also has the lowest cost and better economy of the auxiliary frequency regulation module. The wind power inertia output control scheme based on rotor kinetic energy control is constructed by considering the frequency response characteristics of synchronous generator sets and loads. The minimum inertia demand calculation model of the power system is established with the rate of change of frequency and the maximum frequency offset as constraints. Combined with the real-time operating conditions of the wind turbine, the speed regulation limit of the wind turbine rotor kinetic energy control is obtained to avoid the wind turbine off-grid due to excessive frequency regulation. In order to prevent the frequency secondary drop of the system during the speed recovery process, the steady speed recovery of the wind turbine is controlled by setting the speed change rate. The feasibility of the auxiliary primary frequency regulation strategy proposed in this paper is verified by an example of a two-region four-machine system. When the disturbance sets the sudden load power to 150MW, and under the kinetic energy control of the wind turbine rotor, the system frequency change rate and the maximum frequency offset are obviously increased, especially the maximum frequency offset is reduced by 0.348Hz, which further illustrates the flexibility and plasticity of rotor kinetic energy control of wind turbines. The research results of this paper can provide a theoretical basis for adding additional frequency control to existing wind turbines.